Differing Von Hippel Lindau Genotype in Paired Primary and Metastatic Tumors in Patients with Clear Cell Renal Cell Carcinoma - Vaziri, Susan A.; Tavares, Emmanuel J.; Golshayan, Ali R.; Rini, Brian I.; Aydin, Hakan; Zhou, Ming; Sercia, Linda; Wood, Laura; Ganapathi, Mahrukh K.; Bukowski, Ronald M.; Ganapathi, Ram (Frontiers in Oncology, 2012)
In sporadic clear cell renal cell carcinoma (CCRCC), the von Hippel Lindau (VHL) gene is inactivated by mutation or methylation in the majority of primary (P) tumors. Due to differing effects of wild-type (WT) and mutant (MT) VHL gene on downstream signaling pathways regulating angiogenesis, VHL gene status could impact clinical outcome. In CCRCC, comparative genomic hybridization (CGH) analysis studies have reported genetic differences between paired P and metastatic (M) tumors. We thus sequenced the VHL gene in paired tumor specimens from 10 patients to determine a possible clonal relationship between the P tumor and M lesion(s) in patients with CCRCC. Using paraffin embedded specimens, genomic DNA from microdissected samples (>80% tumor) of paired P tumor and M lesions from all 10 patients, as well as in normal tissue from 6 of these cases, was analyzed. The DNA was used for PCR-based amplification of each of the 3 exons of the VHL gene. Sequences derived from amplified samples were compared to the wild-type VHL gene sequence (GeneBank Accession No. AF010238). Methylation status of the VHL gene was determined using VHL methylation-specific PCR primers after DNA bisulfite modification. In 4/10 (40%) patients the VHL gene status differed between the P tumor and the M lesion. As expected, when the VHL gene was mutated in both the P tumor and M lesion, the mutation was identical. Further, while the VHL genotype differed between the primary tumor in different kidneys or multiple metastatic lesions in the same patient, the VHL germline genotype in the normal adjacent tissue was always wild-type irrespective of the VHL gene status in the P tumor. These results demonstrate for the first time that the VHL gene status can be different between paired primary and metastatic tissue in patients with CCRCC.